The Impact of Foreign-Trade Zones on County Level Development: A Temporal Analysis. (2nd October 2022) - Lane, Jesse M.; Liu, Zhi-Jun
Abstract: In 1934, the Foreign-Trade Zone Act was passed in order to ease restrictions on internationally traded goods, provide domestic firms with a competitive advantage over foreign companies, boost jobs in import/export businesses, increase exports, and promote economic development. The growth in the number of foreign-trade zones (FTZs) across the United States since 1934 has resulted in the ever-expanding reach of the zone program across the landscape. Even with the growth of FTZs, these zones have remained largely obscure to academia and the public at-large. While various scholars have analyzed the impact of FTZs on exports and trade volumes, few have focused on spatial and temporal impacts on neighboring communities. This study analyzed short- and long-term percentage changes in median household income, unemployment rates, number of manufacturing firms, and manufacturing employment after FTZs were added to a county. Results indicate a significant long-term increase in manufacturing employment in counties adding an FTZ but a significant increase in unemployment rates and decline in manufacturing firms in neighboring counties. These findings suggest FTZs may provide manufacturing employment benefits for a county in the long-term but costs on overall employment and number of firms in neighboring counties may outweigh these benefits.